Corporate governance and financial features of Portuguese family firms - Paiva, I. (2020)
This study analyses whether corporate governance and financial features of private family firms are different from private non-family firms and discusses the role of private family firms in regional economic development. The evidence is drawn from a database of Portuguese private family owner-managed firms in order to determine the differences in the management and experiences of venture capital and other financing options. The main results demonstrated that family firms have significantly lower ratios of leverage, are less interested in venture capital, have much more experience in management and are less likely to be female than those in non-family firms. Our results indicate that the financial development of Portuguese private family firms is also consistent with the moderate tenet of family firms which could hamper their business growth and demonstrate that corporate governance features assist the family identity and the ability to exert family influence.